Islamofobia dan Turkofobia di Eropa: Studi Kasus Pembakaran Al-Quran Oleh Rasmus Paludan - Syauqii, Fachri (Medan Resource Center, 2023)
The burning of the Qur'an by Rasmus Paludan reignited Islamophobia. Sweden has a large population of Muslims. Some opinions in various Western media, such as the BBC, considered that the action taken by Paludan was because Sweden was denied membership in the NATO. The author assumes that Paludan's Qur'an burning was purely political and aimed to gain protection from NATO, both in terms of security and economy, but the effort was blocked by Turkey, which is a NATO member and Erdogan suspected that Paludan was working with Kurdish terrorist organizations. This article illustrates how the root causes of the Koran burning case committed by Paludan affected the European community's fear of the development of Islam so that Muslims are not free to practice or express their religious values in public spaces. Various groups reacted strongly to this, including Erdogan, who condemned Paludan’s actions. This article also examines how various groups, including Muslims and the Swedish government, responded to Paludan's actions.